Indonesian Society of Respirology (ISR) Consensus Statement on Lung Cancer Screening and Early Detection in Indonesia - Sita Andarini; Elisna Syahruddin; Nathaniel Aditya; Jamal Zaini; Ferry Dwi Kurniawan; Sabrina Ermayanti; Noni Novisari Soeroso; Sri Melati Munir; Andreas Infianto; Ana Rima; Ungky Agus Setyawan; Laksmi Wulandari; Haryati Haryati; Ida Ayu Jasminarti; Arif Santoso (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Lung cancer is the leading cause of mortality for all cancer globally and in Indonesia. In Indonesia, lung cancer contributes to 12.6% of death of all cancer, making it the number one cause of cancer death, and 8.6% of all cancer incidence in 2018, behind breast, cervical, and colorectal cancer. The total cases per year are expected to almost double from 30,023 in 2018 to 54,983 cases in 2040. Smoking is among the risk factors for lung cancer, after occupational/environmental risk factors, history of lung fibrosis, and family history of cancer. There was a tendency of younger smokers in Indonesia and increased lung cancer incidence and prevalence in the younger population. The median age of lung cancer in Indonesia was younger than in any country, probably due to the younger age of smoking, early onset of carcinogens, asbestos use, and environmental. Lung cancer screening is a voluntary measure to detect lung cancer in the earliest stage, to find cancer at curable disease before symptoms appear in high-risk individuals. Lung cancer early detection is strategies to find cancer earlier after symptoms appear (cough, hemoptysis, dyspnea, chest pain). Low-dose computerized tomography of the thorax (LDCT) screening has been known to reduce lung cancer mortality compared to a chest x-ray (CXR). This Indonesian Society of Respirology consensus statement was aimed to give recommendations on lung cancer screening and early diagnosis in Indonesia.